CFD based evaluation of the serviceability conditions of a cable stayed bridge under wind load - A. V. Lopes (2005)
This paper presents a new methodology for the analysis of serviceability limit states of vibrations caused by wind action on slender structures, based on the appropriate conjugation of an algorithm of Computational Fluid Dynamics (Control Volume Method) with an algorithm of linear or geometrically nonlinear analysis of structures. The computer code developed on the basis of this methodology was applied to the evaluation of the serviceability conditions of a cable stayed bridge with a deck cross-section, under wind load. Some of the most interesting results associated with the evaluation of the corresponding response acceleration are presented and compared with available human body acceptance criteria for vibrations (comfort evaluation) present in the technical literature.